Strongly Pseudo Nearly Semei-2-Absorbing Submodule(I) - Essa Dahash, Mohmad; K. Mohammadali, Haibat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let  be a module over a commutative ring  with identity. In this paper we intoduce the concept of Strongly Pseudo Nearly Semi-2-Absorbing submodule, where a  proper submodule  of an -module  is said to be Strongly Pseudo Nearly Semi-2-Absorbing submodule of   if whenever , for implies that either  or , this concept is a generalization of 2_Absorbing submodule, semi 2-Absorbing submodule, and strong form of (Nearly–2–Absorbing, Pseudo_2_Absorbing, and Nearly Semi–2–Absorbing) submodules. Several properties characterizations, and examples concerning this new notion are given. We study the relation between Strongly Pseudo Nearly Semei-2-Absorbing submodule and (2_Absorbing, Nearly_2_Absorbing, Pseudo_2_Absorbing, and Nearly Semi–2–Absorbing) submodules and the converse of this relation is true under certain condition. Also, we introduced many characterizations of  Strongly Pseudo Nearly Semei-2-Absorbing submodules in some types of modules.